Reproducibility of a 3-dimensional gyroscope in measuring shoulder anteflexion and abduction - Penning, Ludo I F (BioMed Central, 2012)
BACKGROUND: Few studies have investigated the use of a 3-dimensional gyroscope for measuring the range of motion (ROM) in the impaired shoulder. Reproducibility of digital inclinometer and visual estimation is poor. This study aims to investigate the reproducibility of a tri axial gyroscope in measurement of anteflexion, abduction and related rotations in the impaired shoulder. METHODS: Fifty-eight patients with either subacromial impingement (27) or osteoarthritis of the shoulder (31) participated. Active anteflexion, abduction and related rotations were measured with a tri axial gyroscope according to a test retest protocol. Severity of shoulder impairment and patient perceived pain were assessed by the Disability of Arm Shoulder and Hand score (DASH) and the Visual Analogue Scale (VAS). VAS scores were recorded before and after testing. RESULTS: In two out of three hospitals patients with osteoarthritis (n = 31) were measured, in the third hospital patients with subacromial impingement (n = 27). There were significant differences among hospitals for the VAS and DASH scores measured before and after testing. The mean differences between the test and retest means for anteflexion were −6 degrees (affected side), 9 (contralateral side) and for abduction 15 degrees (affected side) and 10 degrees (contralateral side). Bland & Altman plots showed that the confidence intervals for the mean differences fall within −6 up to 15 degrees, individual test - retest differences could exceed these limits. A simulation according to ‘Generalizability Theory’ produces very good coefficients for anteflexion and related rotation as a comprehensive measure of reproducibility. Optimal reproducibility is achieved with 2 repetitions for anteflexion. CONCLUSIONS: Measurements were influenced by patient perceived pain. Differences in VAS and DASH might be explained by different underlying pathology. These differences in shoulder pathology however did not alter the reproducibility of testing. The use of a tri axial gyroscope is a simple non invasive and reproducible method for the recording of shoulder anteflexion and abduction. Movements have to be repeated twice for reproducible results.